Development and optimization of an in vitro cultivation protocol allows for isolation of Borrelia miyamotoi from patients with hard tick-borne relapsing fever. (July 2017) - Koetsveld, J.; Kolyasnikova, N.M.; Wagemakers, A.; Toporkova, M.G.; Sarksyan, D.S.; Oei, A.; Platonov, A.E.; Hovius, J.W.
Abstract: Objectives: Borrelia miyamotoi has been shown to infect humans in Eurasia and North America causing hard tick-borne relapsing fever (HTBRF). In vitro cultivation of B. miyamotoi was described recently; but clinical isolation of relapsing fever Borrelia is cumbersome. Our aim was to develop a straightforward protocol enabling B. miyamotoi isolation directly from the blood of patients. Methods: Modified Kelly-Pettenkorfer (MKP-F) medium, with or without anticoagulants, or blood from healthy human volunteers, was spiked with B. miyamotoi spirochaetes in vitro . Subsequently, either media or plasma was used for cultivation directly, or after an additional centrifugation step. This isolation protocol was tested in a clinical setting on patients suspected of HTBRF. Results: Dipotassium-EDTA, trisodium citrate and lithium heparin inhibited growth of B. miyamotoi at concentrations ≥250 μg/mL, 2.5 mM and 1 IU/mL, respectively. However, when plasma originating from human blood containing B. miyamotoi spirochaetes was subjected to an additional centrifugation step at 8000  g, suspended and inoculated into fresh MKP-F media, positive cultures were observed within 2 weeks. Of importance, this straightforward protocol allowed for isolation of B. miyamotoi from six out of nine patients with confirmed HTBRF. Conclusions: Direct culture from K 2 -EDTA, trisodium citrate and lithium heparin plasma containing B. miyamotoi is hampered due to anticoagulants. Using a simple centrifugation protocol we were able to circumvent this detrimental effect, allowing for the first clinical isolation of B. miyamotoi. This will be of value for future research on the pathogenesis, genetics, diagnosis, therapy and epidemiology of HTBRF and other tick-borne relapsing fevers.